Stability predictions for excavations of mountain tunnels based on [BQ] method and its field verification. (November 2022) - Zhou, Jian; Yang, Xinan; Guo, Jing
Highlights: The maximum load-bearing ratios of the secondary lining for ordinary Class III, seepage Class III and Class IV surrounding rocks are 24.2%, 25.4% and 34.7% respectively. For the Dahongyan Tunnel, the change in the length of the anchors should be adjusted to from 3.0 m to 3.5 m and the distance of the secondary lining from the excavation face changes from 40 m to 46 m. The secondary lining load sharing ratio at the monitoring point of the maximum load of the section secondary lining generally doesn't exceed 35%. Abstract: In response to the engineering problems often encountered during the construction of mountain tunnels, the aim of this study is to overcome the inability of numerical simulation methods to rapidly predict tunnel construction based on the [BQ] method of classifying surrounding rock grades. Numerical simulations were carried out using FLAC3D6.0 software based on previous empirical formulas for each parameter of the GSI scores and Hoek-Brown criterion. Relying on the Luanlu Highway Tunnel Project, the engineering problems of the Nianpan and Dahongyan tunnels were firstly identified, followed by numerical simulations to quickly obtain construction predictions for the proposed changes, and finally, engineering monitoring was carried out to verify the feasibility of the method. The results indicate that [BQ] = 311 for the water gushing section of the Nianpan Tunnel, which should be changed from Class III to IV surrounding rock and constructed according to the support scheme for Class IV surrounding rock, corresponding to GSI[BQ]  = 43. The maximum load-bearing ratios of the secondary lining for ordinary Class III, seepage Class III and Class IV surrounding rocks are 24.2 %, 25.4 % and 34.7 % respectively. For the Dahongyan Tunnel, the change in the length of the anchors should be adjusted to from 3.0 m to 3.5 m and the distance of the secondary lining from the excavation face changes from 40 m to 46 m. Moreover, the secondary lining load sharing ratio at the monitoring point of the maximum load of the section secondary lining generally doesn't exceed 35 %. The method can be used as a reference for other tunneling problems.